Dysplasia epiphysealis hemimelica: A case report - Jovanović, Dalibor V.; Ilic, Milena B.; Milosavljević, Miloš Z.; Mihajlović, Zorica; Vojinović, Radiša H.; Mitrović, Slobodanka Lj.; Azanjac, Goran (Vojnosanitetski pregled, 2014)
Introduction. Dysplasia epiphysealis hemimelica, also known as Trevor’s disease, is an extremely rare skeletal developmental disorder of unknown etiology, characterized by an osteocartilaginous outgrowth of one or more epiphyses or of a tarsal bone during childhood. Case report. We presented a sporadic case of dysplasia epiphysealis hemimelica developed in the talus. A 6-year-old boy complained of swelling of his right ankle joint, with painful and reduced movements. Radiographies suggested excessive overgrowth of the dorsomedial aspect of the talus. The tumor was surgically excised and the gross and histological findings were consistent with those of osteochondroma. Conclusion. Dysplasia epiphysealis hemimelica is diagnosed by clinical, radiographic and histopathological examination. Early diagnosis is important for the condition to be treated before the deformity becomes disabling.